GAMBARAN PELAKSANAAN FUNGSI PERAWATAN KELUARGA PADA ANGGOTA KELUARGA YANG MENDERITA TB PARU DIPUSKESMAS - Fahruddin, Fahruddin; Karim, Darwin; Wahyuni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Pulmonary TB is a contagious infectious disease (acute or chronic) cuased by Mycobacterium Tuberculosis and is characterized by pulmonary infiltration, granulation formation and preparation, fribrosis, and cavitation on infected tissue, and hypersensitivity accompanied cell mediated (cell-mediated hypersencitivity). In 2016 there are 10,4 million pulmonary TB cases in the world, 56% pulmonary TB cases is located in India, Indonesia, China, Philippines and Pakistan. About 1,3 million people in the world passed away because pulmonary TB. Health care and maintenance function is to maintain the health condition of family members in order to still have high productivity. This function was developed into a family task in the health sector. This research functions to find out the description of the implementation family care function for family members who suffer from pulmonary TB. This reserach using descriptive research design. Research sample is 56 respondences taken based on inclusion criteria using Purposive sampling techinque. Measuring instrument used is questionnaire. The analysis used is univariate analysis to know the frequency distribution of research results showed 28 people respondences able to know, to decide, to take care, modify the environment, utilize health facilities (50,0%) and 28 people respondences are not able (50,0%). The results of this research expected to family to implement the family care function to family members especially for family members who suffer pulmonary TB. Â Keywords : Implementation Description, care function family, pulmonary TB